Muscular Behavior during Inspiratory Training in Patients with a Complete Cervical Spinal Cord Injury: Pilot Study - Tomás Santibáñez Arellano (Brazilian Army, 2016)
Introduction: There is a huge variety of inspiratory muscle training protocols in patients with complete cervical spinal cord injury. None of them provide information about muscle behavior and its relationship with effort and fatigue sensation perceived by the subject. Objective: Analyze the relationship between the behavior of the Median Frequency (MF) and the Root Mean Square (RMS) of diaphragm (DPH) and sternocleidomastoid (ECOM) muscles and Subjective Fatigue Sensation (SFS) during an inspiratory muscle training session using a threshold valve in patients with CCSCI. Methods: Electromyographic activity of the DPH and ECOM during a fifteen minutes training session using a threshold valve with a Maximum Inspiratory Pressure (MIP) of 30% was recorded. Median Frequency average and the Root Mean Square of DPH and ECOM was calculated. SFS was recorded every minute. The correlation between variables was determined by Spearman rho. Results: The correlation between SFS and MF of the DPH was 0.22. The correlation between SFS and MF of the ECOM was 0.36. The correlation between SF and RMS_INDEX was -0.09. Conclusion: There is no correlation between the variables studied. The RMS_INDEX is presented as a useful tool to describe the muscle behavior during training with threshold valve.Results: The correlation between SFS and MF of the DPH was 0.22. The correlation between SFS and MF of the ECOM was 0.36. The correlation between SF and RMS_INDEX was -0.09.Results: The correlation between SFS and MF of the DPH was 0.22. The correlation between SFS and MF of the ECOM was 0.36. The correlation between SF and RMS_INDEX was -0.09. Comportamento muscular durante treino inspiratório em pacientes com lesão medular cervical completa: estudo pilotoIntrodução: Existe uma grande variedade de protocolos de treinos inspiratórios em pacientes com lesão medular cervical completa. Nenhum deles passa informação a respeito do comportamento muscular nem sua relação com a sensação de esforço e fadiga percebida pelo sujeito. Objetivo: Analisar a relação entre o comportamento da FM e raiz media quadrática (RMS) de diafragma (DPH) e esternocleidomastóideo (ECOM) e a SSF durante uma sessão de treino de musculatura inspiratória com válvula umbral em pacientes com LMCC. Métodos: Foi registrada a atividade eletromiográfica do diafragma e o esternocleidomastoideo durante quinze minutos de treino com válvula umbral a 30% de PIM. Foi calculada a frequência média e a raiz quadrada média do DPH e ECOM. Foi registrada a SSF a cada minuto. Foi determinada a correlação entre as variáveis mediante rho de Spearman. Resultados: A correlação entre SSF e FM de DPH foi 0.22. A correlação entre SSF e FM de ECOM foi 0.36. A correlação entre SSF e RMS_INDEX foi -0.09. Conclusão: Não existe correlação entre as variáveis estudadas. O RMS_INDEX é apresentado como uma ferramenta útil para descrever o comportamento muscular durante um treino com a válvula umbral.